A Kenyan trilogy - Wawman, Richard; Thornicroft, John; Mohammed, Sadiq ([Windsor, Berks] : Essential TV (Overseas) Ltd., 1990)
Summary : The programmes feature the animals in the wildlife conservation parks in Kenya and the scale of descructive influences man can have the well being of the animals in Africa as a result of the tourism industry.
Contents : programme 1- Carnival of the animals, programme 2- The last ceremony, programme 3- Orphans of Tsavo
Library holding : programme 1- Carnival of the animals
Photography, Roger Wood and Mohinder Dhillon
Narrator: Paul Vaughan
Keywords: Wildlife conservation -- Kenya; Man -- Influence on nature -- Africa